Electronic publishing and its promotional rolein interior Design (Al-Academy, 2024)
Electronic publishing has witnessed a remarkable expansion in an unusual scope, as those interested in this field began to increase, especially the segment of designers, as it began in a regulated manner, but it began to expand due to the important benefits it provides to all fields and to the field of interior design in particular. The current research is interested in studying The active role of electronic publishing in the field of interior design and the great services it provides in transferring and exchanging information and promoting design work completed by designers, whether individuals or companies, specifically for design. The research dealt with four chapters. The first chapter dealt with the research problem, which was defined by asking: Does electronic publishing contribute to promoting the work of the designer? Interior?, and included in its importance the role of publishing in conveying information at an almost record speed, and the goal of the research was evident in revealing the possibilities that electronic publishing provides for the interior designer to publish his work, and included within its objective limits a study of the possibilities of electronic publishing and in the spatial limit the Grand Beijing Airport and in the border The time frame is the period from 2013-2019, which is the period of completion of the project. As for the second chapter, which deals with its first two sections, the concept of electronic publishing, and its second section, techniques and internal spaces, and the means used by the designer that contributed to the speed of completion of the project, from drawing programs and means of communication that the designer used to complete his work. As for the third chapter, procedures. The study and the use of drawing programs that were applied to smart devices and the research sample on which the work was applied was the Greater Beijing Airport. As for the fourth chapter, the researcher discussed the most important findings that she reached, which is that electronic publishing contributed to the rapid transfer and exchange of plans and designs from the parent company to the work sites very quickly.